Konsep Qiyâs dan Maslahah dalam Ijtihad Muhammad Rasyid Ridla - Iman, Fauzul (TAJDID, 2019)
The jurists have different perspectives and method choices in ijtihad. Salaf scholars, who were spearheaded by Imam Ahmad ibn Hanbal and Ibn Taimiyah, tended to use the Koran and as-Sunnah as the basis and main reference in establishing Islamic law. They involved very little ra'yu in performing establishment of law. Even if ra'yu is used in the process of establishment of law, they tend to only choose qiyâs as the only involvement of ra'yu in jijtihad. On the other hand, the jurists who are at the rational pole give a large portion of the role of reason (ra'yu) in jihad. Imam Abu Hanifah, for example, one of the proponents of a rational school of thought, placed ra'yu (istihsân) in the process of establishment of law with a sizable portion, even when compared to the portion of the hadith. This article tries to parse Ridla's thoughts about the position of the Koran, hadith, and ra'yu, both in their position as sources and methods of ijtihad. The results of the discussion concluded that Muhammad Rasyid Ridla fervently fought for the use of the Koran and Hadith as the main basis and reference in jihad, while not being hesitant to use qiyâs and mashlahat as ijtihad methods. For him, ijtihad is a demand for thinking that must be continuously opened and encouraged because it is a dynamic and universal teaching of the Koran. Ridla show that Islam is a dynamic, flexible, and friendly teaching towards the development of society